The effects of the so-called incidental proceedings in Slovak Restructuring Law - Adamus, Rafał (The Opole Studies in Administration and Law, 2019)
This study is devoted to the analysis of Slovak restructuring law limited to the interpretation of § 124 sec. 6 ZoKR. The provisions of Slovak law in relation to claims reported but not recognized in the restructuring proceedings allow creditors to bring legal action against the debtor, under the so-called incidental action. The effects of the court’s decision issued after conducting such proceedings are set out in § 124 sec. 6 ZoKR. The content of the study presents arguments for the thesis that the term “ne mozno voci dlznikovi vymahat”, as used in § 124 para. 6 ZoKR, carries a substantive effect of the expiry of the claim, but as a result of the court’s recognition of the case in an incidental proceedings by virtue of the general procedural rules, it appears – the state of res judicata. From the provision of § 124 para. 6 ZoKR it should be concluded that by the end of the incidental process, the state of lis pendes is updated.